Responsible Behavior and Environmental Protection – in Case of Football Clubs - Kinga Ráthonyi-Ódor; Éva Bácsné Bába; Gergely Ráthonyi (Apstract: Applied Studies in Agribusiness and Commerce, 2019)
There has been a hotspot in sports industry these days that is becoming more and more wide-spread in sports organizations and among managers, namely CSR, that is corporate social responsibility. In the life of geographical regions, towns or villages, professional football clubs play a crucial role. Consequently, clubs tend to take responsibility for these communities in return for their support: whether it is the local population or the authorities, other businesses or the environment, they are ready to stand up for good causes. Nowadays sports centres with their regular events have a significant effect on the environment either regionally or globally. That is the reason why it has become vital in the management of sports facilities to respect environmental principles when designing and using sports facilities and to avoid producing pollution that could harm and deteriorate the environment. The aim of our study was on the one hand, to present the definitional and theoretical evolution of CSR, than the CSR concept in sport, special regard to environmental protection. On the other hand, to analyze what kind of CSR related issues do football clubs (Real Madrid C. F. – RM, Borussia Dortmund – BVB) and how they are addressing issues of environmental sustainability in the context of CSR. According to RM and BVB, we can say that they really try to do efforts to responsible behavior and environmental protection. They have special respect for the society and took big step to use different environmental management tools. It was easy to find information, reports and case studies about these activities.